2015
DOI: 10.1007/s10862-015-9527-5
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analyses of Self- and Parent- Report Inventory of Callous-Unemotional Traits in 8- to 10-Year-Olds

Abstract: The factorial structure of the Inventory of Callous-Unemotional Traits (ICU; Frick 2004) has been inconsistent across various studies using different rater versions and samples. In this study the factorial structure of the self- and parent-report versions of the ICU was examined in a community sample of 340 boys and girls aged 8- to 10-years. A series of confirmatory factor analyses revealed that (1) for self-report ICU, a two-factor model comprising one Uncaring and one Callousness factor fit the data best; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 34 publications
12
64
0
Order By: Relevance
“…Therefore, our final aim was to replicate and extend previous studies’ efforts to explore convergent validity of the parent‐report version of the ICU. Consistent with previous studies such as Gao and Zhang (), Hawes et al. () and Willoughby et al.…”
Section: Current Studysupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, our final aim was to replicate and extend previous studies’ efforts to explore convergent validity of the parent‐report version of the ICU. Consistent with previous studies such as Gao and Zhang (), Hawes et al. () and Willoughby et al.…”
Section: Current Studysupporting
confidence: 93%
“…(), and Horan et al. () found that a bifactor model with callous, unemotional, and uncaring factors had the best relative fit of the models considered in their studies; similarly, Gao and Zhang () found support for this model in a community sample of 8‐ to 10‐year‐old children.…”
Section: Inventory Of Cu Traitsmentioning
confidence: 83%
See 1 more Smart Citation
“…Factor analyses on the current sample supported a modified ICU form with three subscales (callousness, uncaring, and unemotional) (Gao and Zhang 2016). The modified ICU Scores of individual subscales and total ICU score (sum of the three subscale scores) derived from the modified ICU were used in following analyses.…”
Section: Methodsmentioning
confidence: 78%
“…The modified ICU Scores of individual subscales and total ICU score (sum of the three subscale scores) derived from the modified ICU were used in following analyses. The modified ICU is a 19-item scale derived from the APSD to specifically assess callous-unemotional behaviors associated with antisocial personality and has demonstrated convergent validity with existing self-and parent-report measures of psychopathic behaviors (Gao and Zhang 2016). Caregivers are asked how well certain statements describe their child; e.g.…”
Section: Methodsmentioning
confidence: 99%